A Multi-satellite Perspective on “Hot Tower” Characteristics in the Equatorial Trough Zone - Pilewskie, J; Stephens, G; Takahashi, H; L’Ecuyer, T (Springer, 2024)
In 1979, Herbert Riehl and Joanne Simpson (Malkus) analytically estimated that 1600–2400 undilute convective cores vertically transport energy to the tropopause at any given time within a region where upper-tropospheric energy is only exported from the tropics. The focus of this paper is to update this estimate using modern satellite observations, compare hot tower frequency and intensity characteristics to all deep convective cores that reach the upper troposphere, and document hot tower spatiotemporal variability in relation to precipitation and high cloud properties within the tropical trough zone (between 13 °S and 19 °N). Cloud vertical profiles from CloudSat and CALIPSO measurements supply convective core diameters and proxies for intensity and convective activity, and these proxies are augmented with brightness temperature data from geostationary satellite observations, precipitation information from IMERG, and cloud radiative properties from CERES. Less than 35% of all deep cores are classified as hot towers, and we estimate that 800–1700 hot towers occur at any given time over the course of a day, with the mean maximum core and hot tower frequency occurring at the time of year when peak convective intensity and precipitation occur. Convective objects that contain hot towers frequently contain multiple cores, and the largest systems with five or more distinct cores most frequently occur in regions where organized mesoscale convective systems and the highest climatological mean rain rates are known to occur. Analysis of co-located radar and infrared brightness temperatures reveals that passive observations alone are not sufficient to unambiguously distinguish hot towers using simple brightness temperature thresholds.